Reducing Obstacles for Small and Medium Enterprises Via Digitalisation: Albania’s Case - Edlira Llazo; Violeta Neza (Qubahan Academic Journal)
Within the framework of modern economic science, scientists are increasingly focusing on the role of small and medium-sized enterprises. This is determined by the many benefits they provide for the country’s development. Digitalisation is one of the opportunities that can make these structures function more efficiently. Therefore, an assessment of its possibilities for different countries is still relevant. The assessment was made for Albania in the research. The research aims to show the level of digitalisation of small and medium-sized enterprises in the country, as well as to provide recommendations for future policy development in this area. The main research methods used in the study were analysis, forecasting, abstraction. The study describes the role of small and medium-sized enterprises in Albania’s economic development and the importance of digitalisation in facilitating their growth. The study also surveyed more than 100 enterprises and based on selected statistics, described the relationship between marketing budget, years of existence and use of social media. The study also focused on the benefits of digital technologies for organisations, such as the automation of internal processes, and improved communication between the company and potential buyers (target audience). The study provides recommendations for further policymaking in small and medium-sized enterprise (SME) development based on the identified weaknesses of SME development in Albania. This study contributes new knowledge to the field of entrepreneurship development in countries, small and medium-sized companies. In addition, it provides a better understanding of the peculiarities of the Albanian economy.